2004
DOI: 10.1002/anie.200460920
|View full text |Cite
|
Sign up to set email alerts
|

Directing Self‐Assembly of Nanoparticles at Water/Oil Interfaces

Abstract: Finding the right angle: The contact angle of nanoparticles at the water/oil interface can be engineered close to 90° by capping with ligands containing carboxylic ester terminal groups. This drives the nanoparticles to self‐assemble into close‐packed films (see picture), and thus provides the opportunity to create two‐ or three‐dimensional homo‐ or heterogeneous nanostructures for electronic, optoelectrical, and magnetic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
210
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 439 publications
(216 citation statements)
references
References 36 publications
4
210
0
2
Order By: Relevance
“…Jaeger and co-workers demonstrated that highly ordered two-dimensional gold nanoparticle films could be fabricated by a simple direct-drying method, either at the toluene-water interface or toluene-air interface (Figure 7 e, f). [66,67] Other ligand-capped gold nanoparticles, [26,68] FePt nanoparticles, [69] silver nanoparticles, [70] CoPt 3 nanoparticles, [71] and g-Fe 2 O 3 nanoparticles [26] can also self-assemble at the oil-water interface and form thin films.…”
Section: Thin Films At Liquid-liquid Interfacesmentioning
confidence: 98%
See 1 more Smart Citation
“…Jaeger and co-workers demonstrated that highly ordered two-dimensional gold nanoparticle films could be fabricated by a simple direct-drying method, either at the toluene-water interface or toluene-air interface (Figure 7 e, f). [66,67] Other ligand-capped gold nanoparticles, [26,68] FePt nanoparticles, [69] silver nanoparticles, [70] CoPt 3 nanoparticles, [71] and g-Fe 2 O 3 nanoparticles [26] can also self-assemble at the oil-water interface and form thin films.…”
Section: Thin Films At Liquid-liquid Interfacesmentioning
confidence: 98%
“…[21][22][23][24][25] Moreover, similar studies of nanoparticles at interfaces have also been performed in detail for the purpose of constructing hierarchically organized structures. [26][27][28][29] The wettability of a particle surface is described by the contact angle q between the particle surface and the oil-water interface ( Figure 1). This contact angle greatly affects the stabilities of the oil-in-water or water-in-oil emulsions.…”
Section: Thermodynamic Model Of Particles At Interfacesmentioning
confidence: 99%
“…[10,11] We and other groups now have a good understanding of how inorganic NPs can be functionalized so that they are interfacially active in biphasic water-oil systems. [12][13][14][15][16][17][18][19] Previous studies on inorganic NPs capped by stimuli-responsive ligands either have not investigated the interfacial properties of those NPs [20][21][22][23][24] or have focused on the interfacial attachment of NPs to the water/oil interface. [12][13][14][15][16][17][18][19] However, one area that has not been fully investigated is how to make NPs truly "smart" materials that can cross the barriers of biphasic systems, similar to the behavior of biomacromolecules.…”
mentioning
confidence: 99%
“…The most advanced examples have been demonstrated by Emrick, Russell and co-workers 20,35 and M€ ohwald and co-workers. 19,36 However, the unknown stability of the dispersant anchoring groups at the interface combined with limited hydrophobic shell thickness and homogeneity is likely to lead to aggregation at the oil-water interface and precludes the possibility of obtaining particle spacings larger than 1-2 nm. Regarding water soluble NPs, the very limited available examples include 2 nm Au NPs functionalized with short chain alkyl-oligo(ethylene glycol) thiols, 23 8-40 nm charge-stabilized, citrate-capped Au NPs 29 and tobacco mosaic virus.…”
mentioning
confidence: 99%